Pola Asuh Orang Tua Dalam Mengembangkan Sosial Emosional Anak Usia 5-6 Tahun Di Taman Kanak-Kanak Melati Samarinda - Rizky Muhayriah; Happy Liana; Yeni Aslina (BEduManagers Journal : Borneo Educational Management and Research Journal, 2025)
Parental parenting patterns are very important for children and have an impact that lasts into adulthood. Parents need to choose appropriate parenting styles so that children develop good social-emotional behavior. This study aims to find out: (1) How are parental parenting patterns applied at Melati Kindergarten in developing children’s social-emotional skills? (2) What are the supporting and inhibiting factors in the development of children’s social-emotional skills at Melati Kindergarten? This researchuses a descriptive qualitative approach and was conducted at Melati Kindergarten. Data analysis techniques include data reduction, data presentation, and drawing conclusions. The results showed that of the six parents interviewed, three used a permissive parenting style, one used a democratic parenting style, and two used an authoritarian parenting style. Children raisedwith a permissive style tend to be less disciplined, have difficulty regulating themselves, and are not accustomed to following rules. These permissive children tend to be immature and lack self-control. Children raised with a democratic style grow up confident, independent, able to control emotions, and cooperate easily. However, children raised with an authoritarian style tend to be more fearful, less confident, and undisciplined. Regarding supporting and inhibiting factors, internal factors includeparents’ lack of attention, which causes psychological pressure that impacts the child’s mental development. Parents’ busyness results in less support for social-emotional development, causing children to be less responsive to their environment. Poornutrition affects growth and development, making children less focused, easily angered, and fussy. External factors include the surrounding environment, as children adapt to their social environment. Children are excellent imitators.